EFESIENSI DAN EFEKTIFITAS UTILISASI KAMAR OPERASI DI RSUD PERDAGANGAN KABUPATEN SIMALUNGUN TAHUN 2020 - Jeni Mardini (Jurnal Inovasi Kesehatan Masyarakat, 2020)
The operating room is one of the high-cost units but can generate huge profits for the hospital. The challenge of operating room management is to increase the efficiency and effectiveness of the operating room by considering aspects of operating scheduling, operating types and operating room monitoring. This study aims to analyze in depth about the Increased Efficiency and Effectiveness of Operating Room Utilization in Simalungun District Hospital in 2020 using a qualitative descriptive study conducted from January to April 2020. This study used snowball sampling techniques with initial informants totaling 4 people. The results of the analysis concluded that it is necessary to increase the effectiveness and efficiency of operating theater utilities in the General Trading Hospital. Things that need to be done are: Improve SOPs or policies regarding work procedures and service standards in operating room installations, applications to monitor officer functions, provide periodic education and training for officers, Implement periodic maintenance of buildings, Add new / up-to-date equipment operations and support , Implementation of monitoring and evaluation of the quality and quality of operating room installation services on a regular basis.